2008
DOI: 10.1007/s12291-008-0051-1
|View full text |Cite
|
Sign up to set email alerts
|

Normal delivery induced stress alters glutathione peroxidase and TNF-α in elderly primigravidas mononuclear cells

Abstract: To probe the glutathione peroxidase (GPx) activity coupled to ROS and TNF-α

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Oxidative stress often occurs especially after delivery. Noor et al 29 showed TNF-α increased in postpartum caused by increased oxygen consumption and the apnea during uterine contractions. Unfortunately, TNF-α concentration is negatively associated with IGF-1 production 9,30-32 .…”
Section: Resultsmentioning
confidence: 99%
“…Oxidative stress often occurs especially after delivery. Noor et al 29 showed TNF-α increased in postpartum caused by increased oxygen consumption and the apnea during uterine contractions. Unfortunately, TNF-α concentration is negatively associated with IGF-1 production 9,30-32 .…”
Section: Resultsmentioning
confidence: 99%
“…Its ability to catabolize H2O2 is of particular importance in newborns, since their antioxidant enzyme systems in various organs are poorly developed 7 . A study conducted by Noor et al noted that suppression in GPx activity after a spontaneous vaginal delivery is a consequence of extremely high degree of oxidative stress 20 . In our study, the lowest GPx levels were noted among newborns in the SVD group and the highest in the CS-GA group.…”
Section: Discussionmentioning
confidence: 99%